The Position of the Wife as the Primary Breadwinner in the Division of Joint Property: A Legal Review of Decision No. 2388/Pdt.G/2023/PA.Im - Nasution, Zulkifli; Dhiauddin Tanjung,; Hasan Matsum, (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
The shifting role of wives as primary breadwinners within families has become increasingly evident, yet this reality remains insufficiently recognized in the division of joint property upon divorce. Article 97 of the Compilation of Islamic Law (KHI), which mandates equal division, often fails to reflect actual economic contributions, particularly when the wife plays a dominant financial role. Addressing this gap, this normative legal research adopts a qualitative approach through a literature study, utilizing primary legal sources (court decisions, the Marriage Law, KHI, the Qur’an, Hadith, and fiqh principles) and secondary sources (fiqh texts, legal theories, and academic journals). The findings from the Religious Court Decision of Indramayu No. 2388/Pdt.G/2023/PA.Im show that the judges took a progressive stance by allocating 60% of the joint property to the wife and 40% to the husband, though the proportion still falls short of representing the wife’s significant economic contribution as she worked in Hong Kong and financed most of the home construction. From an Islamic legal perspective, justice implies proportionality rather than mere equality, aligning with the concept of syirkah (partnership) and the principles of maqāṣid al-syarī‘ah, which emphasize the protection of property and women’s rights. This study contributes to the reinterpretation of Article 97 of the KHI to be more responsive to contemporary social realities and calls for progressive ijtihād among judges to realize substantive justice in the division of joint property.